TINJAUAN YURIDIS HAK-HAK TERSANGKA DALAM PEMERIKSAAN PENDAHULUAN - Bambang Tri Bawono (Unissula, 2011)
Law enforcement is a process to realize the desires that have positive law through the Act into reality. Thus the issue is a matter of law enforcement efforts to realize these abstract ideas into concrete reality. Inclusion of the right of a defendant to obtain legal aid in the inspection process investigation level in the positive law does not mean that the poem was entitled to them, that the suspect will simply obtain legal assistance from attorneys in the enforcement of legal ideas into reality, there are several factors that influence. These factors can be positive in terms of support, and negative in the sense of inhibiting. An obstacle will result in enforcement of the idea of legal aid can not be realized. Factors affecting the enforcement of legal ideas into reality, that is: (1) substance, (2) the structure and culture (3) the means and facilities. substance associated with the positive aspects of the law that allocates rights legal aid, the structure associated with the institutional mechanism of legal aid providers, the culture associated with the existing values in the circles. institutions, infrastructure and facilities associated with the things that make it possible for an institution to carry out the tasks assigned to him. So although legal aid is certainly one of the rights granted by the positive law, but it's right before the form of abstract ideas.Keyword : Legal Protection, Rights of Suspects, Investigation